PENCIL DRAWING - FINE ART AS A BASIS - Lola Abdurakhimov Xursanovich (American Journals Publishing, 2023)
In this article, pencil drawing as the basis of visual art, realistic depiction of existing things and forms, to develop practical knowledge and skills, as well as aesthetic taste. Love for nature, observation, composition, constructive structure, proportions, perspective, laws of light and shadow are important.
Keywords: Pencil drawing, shape, realistic, existence, composition, perspective, art, artist, dream, sangina, pastel, sauce, pencil, pencil, plaster.